Meta-Analisis Pengaruh penggunaan Model Inquiry Based Learning terhadap Kompetensi Keterampilan Peserta Didik dalam Pembelajaran Fisika - Putri, Yosa Aulya; Usman, Esti Aprilia; Cahyati, Mona Trisna (Jurnal Penelitian Pembelajaran Fisika, 2019)
This research was conducted to analyze the use of Inquiry Based Learning (IBL) models in physics learning in Indonesia. This research method is quantitative descriptive. Reports on the results of this study serve as research subjects. This research method is a meta-analysis with a sample of 10 in national journals. The results showed that the Inquiry Based Learning (IBL) model was implemented through the use of textbooks with a scientific approach and student worksheets so as to improve students' skills well. This meta-analysis research shows that the Inquiry Based Learning (IBL) model is suitable for increasing students' competence in physics learning with effective criteria. so, the learning model can have a good influence on the learning outcomes of physics